Human normal immunoglobulin in the treatment of primary immunodeficiency diseases - Wood, Philip (Dove Medical Press, 2012)
The primary antibody deficiency syndromes are a rare group of disorders that can present at any age, and for which delay in diagnosis remains common. Replacement therapy with immunoglobulin in primary antibody deficiencies increases life expectancy and reduces the frequency and severity of infection. Higher doses of immunoglobulin are associated with reduced frequency of infection. Late diagnosis and delayed institution of immunoglobulin replacement therapy results in increased morbidity with a wide variety of organ-specific complications and increased mortality. Risks of immunoglobulin therapy are minimized by modern manufacturing processes, although patients can experience both immediate and delayed adverse reactions, and concerns remain over the transmission of prions in plasma. Immunoglobulin therapy leads to improvements in overall quality of life, and many of the improvements relate to reduced infection rates and fear of future infections, strongly suggesting that the immunoglobulin therapy itself is the major factor in this improvement. There are limited data on the economic benefits of immunoglobulin therapy, with the fluctuating costs of immunoglobulins making comparison between different studies difficult. However, estimates suggest that early intervention with immunoglobulin replacement compares favorably with prolonged therapy for other more common chronic diseases.